Human resources in the food service and hospitality industry - British Columbia Cook Articulation Committee; BC Open Textbook Project; BCcampus (BCcampus, BC Open Textbook Project, 2014)
"Human Resources in the Food Services and Hospitality Industry is one of a series of Culinary Arts open textbooks developed to support the training of students and apprentices in British Columbia's foodservice and hospitality industry. Although created with the Professional Cook, Baker and Meatcutter programs in mind, these have been designed as a modular series, and therefore can be used to support a wide variety of programs that offer training in foodservice skills."--BC Campus website.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Description based on online resource; title from pdf title page (viewed on January 7, 2016).
Keywords: Food service management -- Textbooks; Personnel management -- Textbooks; Electronic books